Danish community pharmacies supporting self-care for patients - Rikke Nørgaard Hansen; Lotte Stig Nørgaard; Charlotte Verner Rossing (Elsevier, 2023)
In Denmark, self-care has been a part of the health care professional and health political discourse since the middle of the 1970s particularly in relation to prevention. However, the concept has become more visible in connection with the Danish government's public health programme "Healthy throughout life" from 2002 to 2010, where patients' self-care was highlighted as an important element in preventing disease progression and complications. Self-care in Denmark is seen as a partnership between the patient and the health care professional. Some self-care activities in Danish community pharmacies are mentioned in national and municipal guidelines for better prevention and self-care regarding obesity, sexual health, smoking cessation, teaching patients/relatives and vaccination. This paper describes self-care activities and services delivered by Danish community pharmacies gathered from survey results at 33 community pharmacies, oral communication with the Association of Danish Pharmacies and published papers on Danish community pharmacy services.Self-care activities in Danish community pharmacies include counselling (about health, self-care, prescription medication, and OTC medication), health campaigns, collaborations with other health care professionals and patient associations and community pharmacy services, all with the purpose to support correct medication use, medication safety and to contribute to health promotion and prevention. These cover activities on prevention, detection, minor ailments, and chronic disease. Six of ten future community pharmacy contributions to medication safety and prevention in future health care, described by the Association of Danish Pharmacies, are related to community pharmacies' support of patients towards better self-care. In the future, Danish community pharmacies should consider offering self-care activities by expanding existing counselling, community pharmacy services and collaborations. Remuneration also needs to be aligned for the activities to succeed and become an integrated part of prevention packages and national initiatives that support patient self-care.